Dilapidation survey on property and infrastructure at Manjoi, Perak / Muhammad Fakhruddin Zulkefli - Zulkefli, Muhammad Fakhruddin (Universiti Teknologi Mara, Perak, 2018)
First of all, this practical training report is about building Dilapidation Survey. Dilapidation inspections are defined as an inspection and report on the condition of a property at a given point in time. It records any existing damage and the state of any particular aspects of the property that are likely to be affected by construction work, excavation or demolition. This report contain 5 chapter that will discuss about the dilapidation survey. For Chapter 1, I introduce the profile of the company that I had intern which is Jasa Sendi (M) Sdn. Bhd that located at 15A, Jalan SG 3/16, Pusat Bandar Sri Gombak, Batu Caves, Selangor. Besides that, I also include the organization chart and any other information that is related to the company in chapter 1. For Chapter 2, I will explain about building dilapidation survey in literature review. The building Dilapidation Survey is an inspection that need to be carry out on buildings or houses that are located adjacent or nearby to the construction site. Any proposal construction that have been approved must receive full building dilapidation report from building consultant before they can proceed the construction work. For Chapter 3, I will discuss about the project that I had involved since I was in Jasa Sendi (M) Sdn. Bhd. The project that I had choose for my practical report is Building Dilapidation Survey at Manjoi, Perak. Beside that, I also explain how the building dilapidation survey works by following the procedure that Jasa Sendi (M) Sdn. Bhd. used. For Chapter 4, I will discuss about problem and recommendation that I had faced during my internship and during my involvement in the building dilapidation survey at Manjoi, Perak. There are several problem that I and the staff faced during the inspection and we all managed it well until we all completed the dilapidation report.